IMPROVING ENGLISH SPEAKING ABILITY USING THE SNOWBALL THROWING GAMES TECHNIQUE - Dedy Williana; Wibbie Putra Anugrah; Evie Kareviati (IKIP Siliwangi, 2020)
Abstract In this study, the researcher used method Classroom Action Research (CAR) to improve the quality of the learning and teaching processes as well as to detect and solving the problems that found in the teaching and learning process. The subjects of this research were the 34 students in SMK Budi Bhakti Utama Padalarang. The researcher used collaborative action research with some English teachers in the school. In this study, the researcher using the instruments interview and questionnaire test to collecting the data. The test that given to students is pre test and also post test in the and of the class or after the students has a treatment. In this result of the study showed the mean score of pretest is 62.02 to 64.00 and post test’s score reached up to 79.00. It is important to describe that there is a significant improvement of the test. Therefore, the criteria of success had been determined. It is crucial to remember that communicative games have contributed and positive impact on teaching and learning process. The communicative games like snowball throwing game expected to enhance students’ motivation and enthusiasm in learning English. Clearly, It gives positive improvement on students’ confidence and their fluency in speaking skill. In short, communivative games can be describing that the strategy of teaching-learning creates good, enjoyable circumstances and reduces the stress level and boredom in learning process. Keywords: Snowball Throwing, Speaking ,Car How to Cite: Last name-1, Initial First and Middle name-1., Last name-2, Initial First and Middle name-2., & Last name-3, Initial First and Middle name-3. (2017). Title Title Title Title. Infinity, X (X), XX-XX.